The Effectiveness of Leader Negative Affection on Employees Perspective - Fajri, Annisa; Djastuti, Indi (Business, Management & Accounting Journal (BISMA), 2024)
This study investigates the effect of a leader's negative affection expression on the leader's effectiveness by mediating the type of inference. Such mediation have not been widely discussed in the previous literature. The findings of this study show that a leader's negative affection, both directly and via mediating the type of inference (motive and nature), has a negative impact on the leader's efficacy. This study provides evidence that there is a direct and indirect influence on the leader's negative affection expression and the leader's effectiveness. The results of this study are also able to confirm the research gap that there are still inconsistent results from the findings on the negative affection of leaders and their outcomes in the form of leader performance.